Total syntheses of wentilactones A and B, and related norditerpene dilactones. Issue 89 (24th October 2022) - Hou, Wu; Cao, Xin; Xu, Peng; Yu, Biao
Abstract : A divergent approach toward the synthesis of A-ring functionalized tetranorditerpenoid dilactones has been developed, employing 3β-hydroxydilactone 6 as a common precursor which is readily derived from ( S )-Wieland–Miescher ketone. Abstract : Wentilactones A and B, two representative tetranorditerpenoid dilactones with promising antitumor activities, are synthesized for the first time. The synthesis employs 3β-hydroxydilactone 6 as a common precursor, which is derived from ( S )-Wieland–Miescher ketone, and leads easily to derivatives with various modifications on the A-ring, such as CJ-1445, asperolide B, and the unnamed natural congener 4 .